Finance Department Annual Plan 1975-76 Budget-Plan Link Supplement to the Detailed Budget Estimates for 1975-76 Government of Tamil Nadu - Planning Commission (Planning Commission, 1975)
Agricultural and Allied Programmes , Co-Operation and Community Development , Projects Programmes Of Rural Development and Employment , Irrigation and Power , Industry and Mining , Transport and Communications , Social Services
Budget-Plan Link
Government of Tamil Nadu